Coffee producers’ perspectives of blockchain technology in the context of sustainable global value chains - Singh, Christina; Wojewska, Aleksandra N.; Persson, U. Martin; Bager, Simon L. (Frontiers in Blockchain, 2022)
Transparency and equitability are key for improved sustainability outcomes in global value chains. Blockchain technology has been touted as a tool for achieving these ends. However, due to the limited empirical evidence, claims on transparency and sustainability benefits are largely theoretical. We lack an understanding of the benefits and drawbacks for different actors within global value chains and how this affects technology adoption. Addressing this gap, we conduct an empirical study to identify the drivers and obstacles for coffee producers in Colombia in adopting blockchain. We base our research on an event-driven and permissioned blockchain model, specifically designed for this research. Applying the Participation Capacity Framework and conducting semi-structured interviews with coffee producers and key informants, we analyze adoption attitudes towards the blockchain application. We further identify opportunities and drawbacks from the producers’ perspective. The coffee producers generally exhibited enthusiasm about the blockchain application, seeing the potential to improve their production practices. Factors that supported interest in the blockchain project included knowledge about actors and processes in the value chain, commercial advantages through better prices and branding, and the possibility to improve product quality based on feedback. Decisive factors affecting the producers’ intention to participate were economic gains and technology accessibility, in terms of required skills and access to the internet and necessary devices. We further encountered a significant gap between current time spent on documentation practices and time producers were willing to spend on implementing the blockchain, pointing to potential barriers to adoption, the role of change agents such as cooperatives, as well as risks for the long-term viability. We set these findings in the context of the Global Value Chain research, considering the existing power relations in the coffee value chain, and drawing upon the concept of sustainable supplier squeeze. The top-down nature of most blockchain implementation projects raises distributive concerns, as resource investments, implementation burden, and risks are significantly higher upstream, whereas downstream lead firms will benefit most. Based on the findings, we identify potential design dimensions and implementation features that can contribute to materializing producer benefits, thus mitigating the risk of a sustainability-driven supplier squeeze.